Application of big data for national security : a practitioner's guide to emerging technologies /: a practitioner's guide to emerging technologies. (2015) - Akhgar, Babak; Saathoff, Gregory B; Arabnia, Hamid; (Professor of computing), Hill, Richard; Staniforth, Andrew; Bayerl, Petra
No abstract available